Perbankan Syariah: Persepsi dan Identifikasi Faktor-Faktor Penentu - Hendratmoko, Christiawan (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
The choice of consumers in selecting banking institution not only determined by economical factors but also may influenced by non economical factors, such as their attitude and beliefs. This article was based on the research conducted to identify factors that could differentiate consumersâ choice on selecting banking service of syaria banks. In case of syaria bank,there are several dimensions, namely, perception, personal selling, family, cost and benefit, religion and beliefs. Further, there is no relationship between consumerâs perception on interest and the type of bank that they choose. But, it is found that there exist several relationships between several dimensions utilized in the study. Such relationship has been found between the age, income, educational level, occupation and the banking type that they selects. In other word, the majority of consumers did not agree with the interest principle but they still choose to deal with banking institution based on their economic rationale.